Physiological, pathological, and targetable membraneless organelles in neurons - Ryan, Veronica H. (Trends Neurosci, 2019)
Neurons require unique subcellular compartmentalization to function efficiently. Formed from proteins and RNAs through liquid-liquid phase separation, membraneless organelles have emerged as one way in which cells form distinct, specialized compartments in the absence of lipid membranes. We first discuss membraneless organelles that are common to many cell types as well as those that are specific to neurons. Interestingly, many proteins associated with neurodegenerative disease are found in membraneless organelles, particularly stress and transport granules. Next, we review possible links between neurodegeneration and membraneless organelles and the hypothesis that the protein and RNA inclusions formed in disease are related to the functional complexes occurring inside these membraneless organelles. Finally, we discuss the hypothesis that protein posttranslational modifications, which can alter phase separation, can modulate membraneless organelle formation and provide potential new therapeutic strategies for currently untreatable neurodegenerative diseases.